Single-cell landscape of alternative polyadenylation in human lymphoid hematopoiesis - Qiang, Jiaqi; Yu, Shan; Li, Jun; Rong, Yu; Wang, Xiaoshuang; Zhu, Yong; Wang, Fang (Journal of molecular cell biology, 2024)
Alternative polyadenylation (APA) is an essential post-transcriptional process that produces mature mRNA isoforms by regulating the usage of polyadenylation sites (PASs). APA is involved in lymphocyte activation; however, its role throughout the entire differentiation trajectory remains elusive. Here, we analyzed single-cell 3′-end transcriptome data from healthy subjects to construct a dynamic-APA landscape from hematopoietic stem and progenitor cells (HSPCs) to terminally differentiated lymphocytes. This analysis covered 19973 cells of 12 clusters from five lineages (B cells, CD4+ T cells, CD8+ T cells, natural killer cells, and plasmacytoid dendritic cells). A total of 2364 genes exhibited differential 3′-untranslated region (3′UTR) PAS usage, and 3021 genes displayed differential intronic cleavage during lymphoid differentiation. We observed a global trend of 3′UTR shortening during lymphoid differentiation. Nevertheless, specific events of both 3′UTR shortening and lengthening were also identified within each cluster. The APA patterns delineated three differentiation stages: HSPCs, precursor cells, and mature cells. Moreover, we demonstrated that the conversion of naïve T cells to memory T cells was accompanied by dynamic APA in transcription factor-encoding genes (TCF7 and NFATC2IP), immune function-related genes (BCL2, CD5, CD28, GOLT1B, and TMEM59), and protein ubiquitination-related genes (UBE2G1, YPEL5, and SUMO3). These findings expand our understanding of the underlying molecular mechanisms of APA and facilitate studies on the regulatory role of APA in lymphoid hematopoiesis.